Field testing of an onsite sanitation system on apartment building blackwater using biological treatment and electrochemical disinfection. Issue 5 (20th March 2020) - Varigala, Siva Kumar; Hegarty-Craver, Meghan; Krishnaswamy, Srinivas; Madhavan, Prakash; Basil, Milan; Rosario, Praveen; Raj, Antony; Barani, Viswa; Cid, Clement A.; Grego, Sonia; Luettgen, Michael
Abstract : Demonstration of an electrochemical toilet wastewater treatment and disinfection technology at the scale of an apartment building and translation of the system into a commercial product. Abstract : The Closed Loop Advanced Sanitation System (CLASS) was designed to treat, disinfect, and recycle toilet blackwater from existing flush toilets in a multi-story apartment building. Two systems were tested at two unique sites in Coimbatore, India for a combined 7500+ treatment hours resulting in more than 180 000 L of treated water. The CLASS prototypes used a combination of biological pretreatment and electrochemical oxidation processes to produce treated water that nearly met the stringent requirements outlined in the standard ISO 30500. The nutrient and organic loading from the toilet blackwater was predominantly reduced by over 85–95% and 80–87%, respectively, through biological processes that were achieved using either a sequencing batch reactor (SBR, site A) or an anaerobic–aerobic biodigester (EcoSan, site B). Complete disinfection of E. coli with nil CFU per ml was achieved using electrochemical processes that also served to remove the remaining organic and nutrient loading to over 90–96%. The treated water was reused for flushing by the residents of the apartment building for 89 days.